Sustainable strategies for high local youth employment in the construction workforce in Malaysia / Norizzati Ibrahim, Z.Y. Zulkiflee and Atikah Najwa Zainuddin - Ibrahim, Norizzati; Z. Y, Zulkiflee; Zainuddin, Atikah Najwa (Universiti Teknologi MARA, Negeri Sembilan, 2018)
The construction industry in Malaysia is heavily dependent on foreign workers. Unfortunately, it seems that the local youth would prefer to be unemployed rather than be employed in construction sites. Archival data from the Labor Force Survey Report was compiled to determine the trend of youth participation in the construction workforce. The findings indicate that local youth participation has never exceeded 25% of the total construction workforce. An extensive survey was also carried out on youth at vocational training centers to determine their current perception of a career in the construction industry especially in construction sites. Surprisingly, the findings of the survey found that 3'D (difficult, dangerous and dirty) image is no longer a main factor in distracting local youth from pursuing career in the construction workforce. Hence, the strategies have been adopted based on extensive feedback from self-administered questionnaire survey to acquire perception 288 local youth who are taking the non-construction courses at GIATMARA Malaysia. Construction industry experts representing Government Authority, Researcher and contractor were also interviewed to obtain an insight on what went wrong with the previous and current initiatives to attract youth into the construction industry and how things can be done better. This study has attempted to produce more effective and sustainable strategies that can transform the construction industry into a preferred sector of employment for local youth.